The evolution of the global terrorist threat: from 9/11 to Osama bin Laden's death - Hoffman, Bruce; Reinares, Fernando (Columbia studies in terrorism and irregular warfare, 2014)
Introduction / Bruce Hoffman and Fernando Reinares -- In the West -- The evolution of the post-9/11 threat to the U.S. homeland / Lorenzo Vidino -- The 2004 Madrid train bombings / Fernando Reinares -- Operation crevice in London / Peter R. Neumann and Ryan Evans -- Dhiren Barot and operation rhyme / Lindsay Clutterbuck -- The van Gogh murder and beyond / Beatrice de Graaf -- Leadership and the Toronto 18 / Stewart Bell -- Operation pendennis in Australia / Sally Neighbour -- The 7 July 2005 London bombings / Bruce Hoffman -- The 2006 airline plot / Paul Cruickshank -- The foiled attacks in Italy in 2006 / Javier Jordan -- The German "Sauerland" plot, central Asia, and Turkey / Guido Steinberg -- The Danish glasvej case / Michael Taarnby -- The January 2008 suicide bomb plot in Barcelona / Fernando Reinares -- Ansar al-Fatah and "Iraqi" networks in France / Jean-Pierre Filiu -- Outside the West -- Al-Qaeda terrorism in Afghanistan / Seth G. Jones -- Attacks of al-Jemaah al-Islamiyah in southeast Asia / Rohan Gunaratna -- The Mombassa attacks of November 28, 2002 / Jonathan Fighel -- The origins of sectarian terrorism in Iraq / Mohammed M. Hafez -- The November 2003 Istanbul bombings / Guido Steinberg and Philipp Holtmann -- The Sinai terrorist attacks / Holly L. McCarthy and Ami Pedahzur -- Comparing the 2003 and 2007 incidents in Casablanca / Jack Kalpakian -- The 2007 suicide attacks in Algiers / Anneli Botha -- The 2003 Riyadh and 2008 Sanaa bombings / Thomas Hegghammer -- The 2008 Mumbai attack / C. Christine Fair -- The 2010 suicide attacks in Kampala / Anneli Botha -- Conclusion / Bruce Hoffman and Fernando Reinares -- List of contributors -- Index